The Effectiveness of In-Game Advertising - Sinai Audhy, Shruti Raghuvir (2010)
This research explores the effectiveness of in-game advertising. Technological advances have rendered traditional advertising obsolete, leading marketers to seek new channels to reach out to the end consumer. New generation computer games and the rise and reach of the gaming industry have transformed this medium into a potential brand placement tool. A number of researchers have endeavoured to study the effectiveness of this form of marketing communication. However, the current research is limited in its knowledge about the effect on a gamer‘s brand memory and attitude.